Manifestation Tolerance at Hok Tik Bio Pati Temple in Interfaith Social Relations - Nilam, Erin Yestia; Mustofa, Moh. Solehatul; Priyanto, Agustinus Sugeng (JESS (Journal of Educational Social Studies), 2023)
Social relations between religious communities are generally not easy because of differences in backgrounds. Inter-religious ties are prone to conflict. Communities in the Pati district can interact despite differences in ethnicity and religion. Inter-community interaction can be seen through activities at the Hok Tik Bio temple, Pati Regency. The Hok Tik Bio temple is active in social-based religious activities for inter-religious people. This study used qualitative research methods. This research focuses on the manifestation of tolerance at the Hok Tik Bio temple in Pati Regency in interfaith social relations. The study shows that religious toleration images are realized through religious celebrations at the temple or non-religious celebrations for the temple's people, such as natural disaster assistance, distribution of takjil in the month of Ramadan, free vaccines, and others. The Pati district community accepted the activities held at the Hok Tik Bio temple by attending in an orderly manner and helping each other. The community was very enthusiastic because the action was suitable for teaching tolerance. The government also contributes by permitting activities and attendance.